Mouthpart morphology of phyllosoma of the tropical spiny lobster Panulirus homarus (Linnaeus, 1758) - Chakraborty, Rekha D.; Radhakrishnan, E. V.; Sanil, N. K.; Thangaraja, R.; Unnikrishnan, C. (Indian Journal of Fisheries, 2011)
Mouthpart morphology of Panulirus homarus phyllosoma larva was studied under scanning electron microscope in order to analyse the developmental changes during growth. Phyllosoma larvae have six pairs of mouthparts (mandibles, maxillule, maxilla, maxillipeds I, II, and III), labrum, and paired paragnaths. Increased length of second and third maxillipeds in late stage phyllosoma resulted in the increase of oral field, thus increasing its ability to catch prey. Labrum and paired paragnaths form a semienclosed oral chamber where mastication by the mandibles occurs. The improved threshing and tearing efficiency in late instars (stage VI-VIII) is facilitated by morphological changes in the mouthparts viz., increase in oral field, increased robustness and number of spinose setations of maxillule, and lengthy maxillipeds, indicating that the late instar larvae can process fleshier prey as compared to the early instar counterparts.